APLIKASI VIRTUAL GAME KARTU KEJUJURAN MENGGUNAKAN ADOBE FLASH CS3 - Astuti, Erni; Sutanta, Edhy; Lestari, Uning (Jurnal Script, 2013)
ABSTRACTÂ Application of virtual card games honesty is a card game for children users is implemented on a computer using Adobe Flash CS3 software. This game uses cards with special design drawings using bright colors that fit with the character of children. Honesty card game aims to train a child to tell the truth to the actual conditions experienced. Honesty card games include questions related to good character, such as honest, loving environment, mutual cooperation, and friendship that should be answered by the player. The game also comes with a honesty card narrative story that will appear after the game is finished. The narrative story is a series of stories made up by a kid who wins the game. Honesty card game is designed to cover 4 story, consisting of 4 different kinds of basic colors, and 100 questions. This game can be played by two or three players. Honesty card games has been practiced by children Tempursari Elementary School to see what the kids about honesty game applications. The test results showed the application, the results of the 10 respondents 90% of children said that the application is easy to use and can capture the information conveyed through honesty card game apps, 80% of children claimed to understand the storyline in the game is good, 100% of children stated design view interesting applications, as well as 80% of children said that the application deserves played by children.Â Keywords : virtual card games honesty, ADOBE FLASH CS3